Evaluation of Corrosion Inhibition of Mild Steel in 1 M Hydrochloric Acid Solution by Mollugo cerviana. (21st July 2014) - Arockiasamy, P.; Sheela, X. Queen Rosary; Thenmozhi, G.; Franco, M.; Sahayaraj, J. Wilson; Santhi, R. Jaya
Abstract : The inhibiting effect of methanolic extract of Mollugo cerviana plant on the corrosion of mild steel in 1 M HCl solution has been investigated by different techniques like potentiodynamic polarization, electrochemical impedance spectroscopy, and weight loss methods for five different concentrations of plant extract ranging from 25 to 1000 mg/L. The results indicated that the corrosion inhibition efficiency increased on increasing plant extract concentration till 500 mg/L and decreased on further increasing concentration. The extract was a mixed type inhibitor with the optimum inhibition concentration of 500 mg/L in potentiodynamic polarization. The adsorption of the plant extract on the mild steel surface was found to obey Langmuir adsorption isotherm. Surface analysis was also carried out to find out the surface morphology of the mild steel in the presence and in the absence of the inhibitor to find out its efficiency. The obtained results showed that the Mollugo cerviana extract acts as a good inhibitor for the corrosion of mild steel in 1 M HCl solution.